Pengaruh penambahan Konsentrasi Reverse Demulsifier terhadap Nilai oil content dan Emulsion Block pada Air injeksi lapangan Jambi - Dahrul Effendi; Fidya Varayesi (BBPMGB LEMIGAS, 2022)
Injection water used as a pressure fluid in water flooding have an impact in its quality problems, consist of oil content and emulsion block. because the oil acts as an adhesive on the solids can causes blockages in the pores of the rock. This has the potential to cause low oil recovery factor in the water flooding process. The injection water (IW) and formation water (FW need to be analyzed in the laboratory before being injected into the reservoir with the aim that the injection water can be used as a pressure fluid in the water flooding process. Based on the results of laboratory tests, injection water (IW) shows a high concentration of oil content (50.55 mg/L) so that it can form emulsion blocks,and can cause plugging in rock pores. For this reason, the solution chosen to solve the emulsion block problem in this study is to use chemical treatment. The problem of oil content and emulsion block can be overcome by using a reverse demulsifier, at a concentration of 50 mg/L the reverse demulsifier can improve the injection water quality from poor water quality (oil content 50.55 mg/L) to good water quality (oil content 15.89 mg/L).